Polarization-dependent plasmonic heating in epitaxially grown multilayered metal–organic framework thin films embedded with Ag nanoparticles. Issue 6 (6th March 2023) - Okada, Kenji; Mashita, Risa; Fukatsu, Arisa; Takahashi, Masahide
Abstract : Polarization-dependent plasmonic heating by lasers in a multilayered metal–organic framework (MOF-on-MOF) oriented film embedded with silver nanoparticles, paving the way for MOF-based thin-film devices with temperature-controllable electrical and optical properties. Abstract : The development of metal–organic framework (MOF) thin films with various functionalities has paved the way for research into a wide variety of applications. MOF-oriented thin films can exhibit anisotropic functionality in the not only out-of-plane but also in-plane directions, making it possible to utilize MOF thin films for more sophisticated applications. However, the functionality of oriented MOF thin films has not been fully exploited, and finding novel anisotropic functionality in oriented MOF thin films should be cultivated. In the present study, we report the first demonstration of polarization-dependent plasmonic heating in a MOF oriented film embedded with Ag nanoparticles (AgNPs), pioneering an anisotropic optical functionality in MOF thin films. Spherical AgNPs exhibit polarization-dependent plasmon-resonance absorption (anisotropic plasmon damping) when incorporated into an anisotropic lattice of MOFs. The anisotropic plasmon resonance results in a polarization-dependent plasmonic heating behavior; the highest elevated temperature was observed in case the polarization of incident light is parallel to the crystallographic axis of the host MOF lattice favorable for the larger plasmon resonance, resulting in polarization-controlled temperature regulation. Such spatially and polarization selective plasmonic heating offered by the use of oriented MOF thin films as a host can pave the way for applications such as efficient reactivation in MOF thin film sensors, partial catalytic reactions in MOF thin film devices, and soft microrobotics in composites with thermo-responsive materials.